Gênero, feminismo e empoderamento da mulher: um estudo sobre a compreensão das estudantes do Ensino Médio - Bianchi, Marília Fortes (2018)
This research was carried out with second and third year high school students from two public schools in the west ofSanta Catarina, in order to understand what they understand by gender, feminism and women's empowerment, and whether or not the school contributed to this understanding. The methodology used for this was the holding of focus groups with the students; talks with school managers and teachers to see if there are any projects related to the subject in schools; and literature review, in order to analyze the data from a well-delineated theoretical framework. This work also aims to problematize the historical relationship of women with education, its main challenges and achievements. Also problematizes the approach of the gender theme in Brazilian education, in view of the growing conservative wave that has criminalized this debate in schools. The research showed that even though they are present in the main documents that regulate basic education curricula in Brazil, gender issues are not being adequately addressed in schools, impairing students' understanding and contributing to the perpetuation of thoughts and macho and prejudiced attitudes, even on the part of the teaching staff, and the pedagogical coordination of schools. This is a major problem, since this is one of the causes of discrimination and harassment that several of the participants have already claimed to have been victims. Machismo presents itself in the lives of students in a variety of ways and in different settings, further reinforcing the urgency of addressing the issue in the classroom as an attempt to turn this reality so damaging to women andother minorities.